Duolandrevus (Eulandrevus) meiacanthus Ma & Dai, sp. nov., a new species of Landrevinae from Yunnan, China (Orthoptera: Gryllidae) - Dai, Jin-Hong; Wang, Ning; Wang, Rui; Ma, Li-Bin (Zootaxa, 2025)
Of the genus Duolandrevus Kirby, 1906, the subgenus, Duolandrevus (Eulandrevus) Gorochov, 1988, has the richest representation in China (11 species currently recorded). Here, we add a new species, Duolandrevus (Eulandrevus) meiacanthus Ma & Dai, sp. nov., to this subgenus from Yunnan, China. The new species resembles Duolandrevus (Eulandrevus) paradoxus (Gorochov, 2001) and can be distinguished by its longer and wider epiphallus and very short epiphallic median lobes. Here, we describe and illustrate this new species.